An Analysis of the Concepts of Vegetarianism and Non-killing as Found in the Śūraṅgama Sūtra - Su, ZHENZHEN; Pannengpetch, Yueng (วารสารพุทธศาสตร์ศึกษา, 2026)
This article examines the concepts of vegetarianism and non-killing as articulated in the Śūraṅgama Sūtra, with the aim of clarifying their ethical and soteriological significance within Mahāyāna Buddhism. The study pursues three objectives: 1) to study the foundational Buddhist principles of vegetarianism and non-killing. 2) to explore the historical background, main content, and significance of the Śūraṅgama Sūtra . 3) to analyze the concepts of vegetarianism and Non-killing as found in the Śūraṅgama Sūtra. Employing textual and doctrinal analysis, this documentary study demonstrates that non-killing, grounded in the first precept, constitutes the ethical foundation of Buddhist moral discipline, while vegetarianism functions as its practical extension, embodying compassion and karmic responsibility. Its results revealed that 1) On the foundational Buddhist principles of vegetarianism and non-killing, it was found that Buddhist ethics takes non-killing as its fundamental principle, aiming to respect life, purify body and mind, and weaken the afflictions that sustain Saṃsāra. Within this ethical framework, vegetarianism functions as the concrete daily practice of non-killing, and Mahāyāna Buddhism, grounded in universal compassion, establishes it as an active ethical responsibility rather than a merely optional moral choice. The doctrines of karma and rebirth further confer soteriological significance upon dietary conduct, as meat consumption perpetuates karmic continuity and saṃsāra, whereas vegetarianism helps interrupt cycles of harm. 2) Through close textual analysis, it was found that Buddhist ethical cultivation is inseparable from meditative and liberative aims. Ethical purity is not treated as an external moral requirement, but as a necessary condition for the purification of consciousness and the realization of authentic meditation, thereby integrating dietary ethics into the broader path of liberation. 3) On the concepts of vegetarianism and non-killing as found in the Śūraṅgama Sūtra, it was found that the text explicitly affirms vegetarianism as an indispensable condition for genuine samādhi, wisdom, and liberation. As a seminal scripture integrating moral discipline (śīla), meditative concentration (samādhi), and wisdom (prajñā), the Śūraṅgama Sūtra clearly states that those who fail to eradicate the mind of killing and continue to consume meat cannot attain authentic meditation or liberation, thereby establishing vegetarianism as a necessary prerequisite for release from saṃsāra.